Network Analysis in Clinical Research in the COVID-19 Context - Cristian Antony Ramos Vera (Revista Finlay)
Network analysis offers a valuable methodological and practical contribution in the health sciences. This analysis enables clinical professionals to be in charge of interpreting and translating the information derived from their research into better comprehensive care in the clinical population of interest, allowing them to focus on a specific intervention based on network results, from the perspective of complex model systems. The evaluation of the network consolidates a greater explanation of the various health conditions functioning linked to the COVID-19 impact and expresses how its etiological mechanisms interact with each other.